EFFECT OF ALGINATE/CALCIUM CONCENTRATION ON PHYSICAL AND SENSORY PROPERTIES OF FAT EXTENDERS - PACHECHO P., Waldir A.; RESTREPO M., Diego A.; LÓPEZ V., Jairo H. (Vitae, 2012)
The fat extenders are fat replacer that can be used to provide some or all of the functions of fat in the meat products, yielding fewer calories than fat. The influence of several sodium alginate (0.69% - 2.81%) and calcium carbonate (0.21% - 0.84%) concentrations on the texture, melting point, and sensory properties of fat extenders made from pork back fat, and a mixture of the above two variables have been studied using a central composite rotable design and response surfaces. Sodium alginate and calcium carbonate concentration revealed a significant effect (p ≤ 0.05) on the texture parameters. In melting properties, there were not significant effects (p ≤ 0.05) on the established limit for variables, except for melting peak temperature. In sensory attributes, they had significant differences (p ≤ 0.05) between fat extenders and the standard, in regard to shine, color and hardness. Therefore, fat extenders made with the addition of 1.0% sodium alginate and 0.79% calcium carbonate displayed textural and melting point properties with higher values in comparison with other treatments, along with sensory characteristics closer to the standard.